Cntnap2 loss drives striatal neuron hyperexcitability and behavioral inflexibility - Katherine R Cording; Emilie M Tu; Hongli Wang; Alexander HCW Agopyan-Miu; Helen S Bateup (eLife)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by two major diagnostic criteria – persistent deficits in social communication and interaction, and the presence of restricted, repetitive patterns of behavior (RRBs). Evidence from both human and animal model studies of ASD suggests that alteration of striatal circuits, which mediate motor learning, action selection, and habit formation, may contribute to the manifestation of RRBs. CNTNAP2 is a syndromic ASD risk gene, and loss of function of Cntnap2 in mice is associated with RRBs. How the loss of Cntnap2 impacts striatal neuron function is largely unknown. In this study, we utilized Cntnap2-/- mice to test whether altered striatal neuron activity contributes to aberrant motor behaviors relevant to ASD. We find that Cntnap2-/- mice exhibit enhanced cortical drive of direct pathway striatal projection neurons (dSPNs). This enhanced drive is due to increased intrinsic excitability of dSPNs, which make them more responsive to cortical inputs. We find that Cntnap2-/- mice exhibit spontaneous repetitive behaviors, increased motor routine learning, perseveration, and cognitive inflexibility. Increased corticostriatal drive may therefore contribute to the acquisition of repetitive, inflexible behaviors in Cntnap2 mice.